Soluble endoglin as a biomarker of successful rheopheresis treatment in patients with age-related macular degeneration - Vladimir Blaha; Jana Urbankova Rathouska; Hana Langrova; Milan Blaha; Jan Studnicka; Ctirad Andrys; Veronika Loefflerova; Miriam Lanska; Eva Vejrazkova; Petr Nachtigal; Alexandr Stepanov (Scientific Reports, 2024)
Abstract Age-related macular degeneration (AMD) is a progressive chronic disease causing visual impairment or central vision loss in the elderly. We hypothesized that successful rheopheresis would be associated with positive changes in soluble endoglin (sENG), PSCK9, alpha-2-macroglobulin (A2M), and hs-CRP levels. 31 elderly patients with the dry form of AMD, treated with rheopheresis with a follow-up period of at least 5 years and an average age of 68 ± 4 years, were evaluated. Each treated patient received a series of 8 procedures in 10 weeks and, after the 2-year period, another 2 procedures within 1 week. Then, the patients were followed up every 6 months and divided into the successfully treated and therapeutic failure group according to best-corrected visual acuity (BCVA), size of the drusen area, and the drusenoid pigment epithelium detachment (DPED). Based on the ophthalmological assessment, rheopheresis treatment was successful in 73% of AMD patients. The therapy was associated with a significant decrease in total cholesterol, LDL-C, HDL-C, apoprotein B, lipoprotein (a) levels, and rheologically important parameters, irrespective of the therapy’s success or failure. The success of rheopheresis therapy was exclusively related to a significant decrease in sENG and A2M levels. Over the long term, rheopheresis prevented the decline of BCVA, reduced the DPED and area of macular drusen, and improved the preservation of an intact photoreceptor ellipsoid zone in most patients. Moreover, we showed for the first time that sENG and A2M could be potentially sensitive biomarkers of successful rheopheresis procedure, irrespective of lipid parameters changes.